Teaching a Threatened Sea: Ecocriticism, Literature, and Environmental Education in High School - Widya Ariska; Solongo Lkhagvadorj; Ndeche Chinyere .C. (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to identify and describe the environmental issues represented in the novel Sampah di Laut, Meira by Mawan Belgia and to determine the implications of these ecocritical representations for Indonesian literature learning in Grade XII of senior high school. Methodology: This research employed a descriptive qualitative method using the novel Sampah di Laut, Meira as the primary data source. Data were collected through reading and note-taking techniques, and analyzed using Miles and Huberman’s procedures: data reduction, data display, and conclusion drawing. The study used documentation tools and manual coding without software assistance. Main Findings: This research employed a descriptive qualitative method using the novel Sampah di Laut, Meira as the primary data source. Data were collected through reading and note-taking techniques, and analyzed using Miles and Huberman’s procedures: data reduction, data display, and conclusion drawing. The study used documentation tools and manual coding without software assistance. Novelty/Originality of this study: This study offers originality by applying ecocriticism to a contemporary Indonesian novel centered on marine pollution, highlighting how literary narratives can raise environmental awareness. It also presents a pedagogical contribution by demonstrating how ecocritical analysis can be integrated into senior high school literature learning, thus enriching students’ ecological literacy and expanding the application of ecocriticism in Indonesian education.